EXPLORATION OF TEACHER'S READINESS IN MATHEMATICS LEARNING IN THE MERDEKA CURRICULUM SMA PANJURA MALANG - Islamiyah, Makhabbatul; Setianingsih, Tri; Mukti, Taufiq Satria (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Curriculum changes caused by the transition of the Indonesian education system are demands that must be implemented to realize the quality of the nation's competitive children. With the implementation of the Merdeka curriculum, teachers pay more attention to the proportion of character strengthening, evaluation of learning and presentation of relevant problem-based learning materials. There are many challenges in realizing an merdeka curriculum in mathematics learning. An merdeka curriculum must be pursued by the entire academic community, especially teachers, to be able to solve educational problems. The purpose of this research to analyze the readiness of mathematics teachers in facing an merdeka curriculum in terms of the learning process and the responses of mathematics teachers. Qualitative research with case studies was conducted at SMA Panjura Malang on mathematics subject teachers. The research instrument is the author himself with the help of documentation in the form of audio and visual. The data processing of the interview results was carried out using descriptive techniques. This data analysis is inductive by using the Miles and Huberman model, namely the interactive model. Activities in this data analysis are data collection, data reduction, data display, and then ends with verification or drawing conclusions. Result an discussion of this study describe that A case study conducted at SMA Panjura Malang related to readiness in implementing an merdeka curriculum shows that the school has a fairly good readiness in terms of the Implementation of the Merdeka Curriculum level 1. This can be proven from the preparation process by holding workshops, preparing teaching modules, teaching linking mathematics in contextual life, opening up free time to provide opportunities for students to discuss, to grow the character of the Pancasila Youth Profile who previously experienced problems due to learning loss.